The pottery finds from the western canabae legionis at Nijmegen (NL): Some methods for spatial and chronological analysis - Polak, Marinus (Rei Cretariae Romanae Fautorum Acta, 2017)
In 1987–1997 Radboud University has carried out a large excavation in the eastern part of Nijmegen, on the site of the Canisiuscollege, a former boarding school. In the excavated area, measuring c. 3.5 ha, remains of three archaeological complexes have been uncovered: – a 42 ha large military base from the Augustan period; – a pre-Flavian cemetery belonging to the civil settlement identified with Oppidum Batavorum; – the canabae legionis surrounding the legionary fortress of Legio X Gemina and its successors, dated to the Flavian period and 2nd century.